A study of a challenges for an unmanned aerial vehicles (UAVs) development - Azlan, Abd Ghani; Hazry, Desa, Prof. Madya Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.